An interdisciplinary regional groundwater model: A study of the Ogallala in the Texas High Plains. Issue 1 (9th January 2013) - Das, Biswa; Willis, David; Rainwater, Ken
Abstract Groundwater research in the Texas High Plains (THP), where production agriculture depends on the Ogallala aquifer, has been conducted by economists, hydrologists and environmental scientists, each focusing on disciplinary aspects of water use, including conservation cost, level of conservation achieved, long‐term aquifer sustainability and water quality degradation. Due to paucity of data, economists often make stringent and unrealistic assumptions concerning the uniformity of aquifer characteristics, land use and water use practices. To address modelling sensitivity to the assumption that aquifer characteristics are homogeneous we develop an integrated regional water policy model for the THP that links a groundwater hydrology model with a dynamic economic optimization model. We compare baseline water use projections provided by a stand‐alone normative economic model to those provided by an integrated economic and hydrologic model that controls for spatial variability in aquifer characteristics. Findings suggest the stand‐alone economic model generally overstates baseline economic returns to water and the water use level compared to the integrated model. The integrated modelling framework controls for the impact spatially heterogeneous aquifer characteristics have on the optimal use of limited groundwater supplies. Improved county‐level estimates for expected baseline economic returns to, and water use by irrigated agriculture over time enhances the ability of water policy‐makers to more precisely model the economic cost and water savings of proposed water conservation policies because policy cost‐effectiveness is normally measured relative to the baseline condition.